Kesesuaian Nilai Religius dan Visual Sentimental Menggunakan Konsep Maslahah Mafsadah dalam Film Siksa Kubur - Fadia Raihan Aqrandista; Sari Riska Rosmiati; Fachri Rachmat Afrizal; Tenny Sudjatnika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the tension between religious narratives and sentimental visuals in Joko Anwar’s film Siksa Kubur (2024), using an ushul fiqh approach and literary analysis. Through a multidisciplinary lens, this study analyzes how several visuals or scenes depicted in the film negotiate the depiction of siksa kubur from fiqh, thereby giving rise to two statements in the concept of ushul fiqh, namely maslahah and mafsadah. The findings reveal the extent to which visual components demonstrate the nature of maslahah and mafsadah while comparing the strength of these two characteristics in the film Siksa Kubur.